2019
DOI: 10.1111/jam.14475
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput analysis of genes involved in biocontrol performance ofPseudomonas fluorescensNBC275 against Gray mold

Abstract: Aims: Many physiological and microbial characteristics influence the biocontrol performance of the biological control agents (BCAs) in agricultural fields. To implement effective biocontrol, the contribution of specific genes, mechanisms and traits to the biocontrol performance of BCAs need to be characterized and explored in greater detail. Methods and results: In this study, a transposon (Tn) mutant library using the BCA Pseudomonas fluorescens NBC275 (Pf275) was generated to explore genes and bacterial char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…We previously confirmed the role of pyoverdine in antagonism and biocontrol efficacy of Pf275 with mutants in genes pvdI and pvdD ( Dutta et al, 2019a ). In this study, antiSMASH identified two BGCs for pyoverdine (clusters 3 and 11) in Pf275 genome with conserved chromophore biosynthetic gene pvdL ( Gross and Loper, 2009 ) in both clusters.…”
mentioning
confidence: 53%
See 4 more Smart Citations
“…We previously confirmed the role of pyoverdine in antagonism and biocontrol efficacy of Pf275 with mutants in genes pvdI and pvdD ( Dutta et al, 2019a ). In this study, antiSMASH identified two BGCs for pyoverdine (clusters 3 and 11) in Pf275 genome with conserved chromophore biosynthetic gene pvdL ( Gross and Loper, 2009 ) in both clusters.…”
mentioning
confidence: 53%
“…In our previous studies, P. fluorescens NBC275 (Pf275) showed strong antagonism against several plant fungal pathogens ( Dutta et al, 2019b ) and biocontrol activity against gray mold in pepper fruit. In addition, overall analysis of Tn-mutant library of Pf275 revealed that production of antifungal SMs contributes to the strain’s biocontrol performance ( Dutta et al, 2019a ). However, the functional roles of the genes and SMs towards antagonism and biocontrol performance remain unclear.…”
mentioning
confidence: 99%
See 3 more Smart Citations